2021
DOI: 10.1038/s41467-021-23490-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular basis of acid taste sensation in Drosophila

Abstract: Acid taste, evoked mainly by protons (H+), is a core taste modality for many organisms. The hedonic valence of acid taste is bidirectional: animals prefer slightly but avoid highly acidic foods. However, how animals discriminate low from high acidity remains poorly understood. To explore the taste perception of acid, we use the fruit fly as a model organism. We find that flies employ two competing taste sensory pathways to detect low and high acidity, and the relative degree of activation of each determines ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Recent studies (including this study) have proposed that sour sensation is quite complex in flies compared with sugar or bitter sensation ( Ganguly et al, 2021 ; Mi et al, 2021 ; Rimal et al, 2019 ; Stanley et al, 2021 ). Wild-type females prefer acid-laced food to lay eggs, which is mediated by the expression of IR25a and IR76b in the GRNs of the tarsal segment ( Chen and Amrein, 2017 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Recent studies (including this study) have proposed that sour sensation is quite complex in flies compared with sugar or bitter sensation ( Ganguly et al, 2021 ; Mi et al, 2021 ; Rimal et al, 2019 ; Stanley et al, 2021 ). Wild-type females prefer acid-laced food to lay eggs, which is mediated by the expression of IR25a and IR76b in the GRNs of the tarsal segment ( Chen and Amrein, 2017 ).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies on IRs and GRs have not been able to conclusively demonstrate their role as molecular sensors for sour taste because none of these studies have demonstrated the direct activation of the IRs by acid. Recently, however, several studies have proposed otopetrin (i.e., a proton-selective channel protein) as a molecular sensor of sour taste in mammals and flies ( Ganguly et al, 2021 ; Mi et al, 2021 ; Tu et al, 2018 ). These studies have demonstrated the direct activation of the otopetrin channel coupled with deficits in acid-mediated behavior, suggesting that this evolutionarily conserved channel protein has a role in proton sensing.…”
Section: Discussionmentioning
confidence: 99%
“…However, biophysical and mice gene studies have refuted these claims (Horio et al., 2011; Richter et al., 2004). New insights may be revealed after the recent discovery of a binary acid‐sensing mechanism in insects that may be evolutionarily conserved, and would involve mammalian homologs of the fly otopetrin family (Mi et al., 2021). Indeed, the protein Otopetrin‐1 (Otop1) is most promising as sour taste receptor (Tu et al., 2018).…”
Section: Taste Receptionmentioning
confidence: 99%
“…Additionally, the role of Otopetrin-like a (OtopLa), a protein confined to the tips of a new class of GRNs in acid-sensing, has been discovered. It was observed that the OtopLa functions as a cation channel, and is involved in the attractive sensing of low levels of acids [227]. However, another new report has also discovered the essentiality of OtopLa in eliciting a repulsive behavioral response to food with a high acid content [228].…”
Section: Gustatory Receptors (Grs)mentioning
confidence: 99%